CAR RENTAL SYSTEMS ON TOUR TRAVEL WAIKIKI USING MICROSOFT VISUAL BASIC 6.0 AND ACCESS - Landam M Simanjuntak; Don Elsyafitra, SKom (Jurnal Sistem Informasi, 2009)
Information System application form is needed to improve effectiveness and tosupport decision making, therefore rental application is needed in raising theperformance of those activities.By using Visual Basic 6.0 to make the car rental application, the system reliability indisplay and data processing can be performed optimally.